Epizootology of Brazot’s Disease in Sheep - Hazratkulov Ismat Aliyar; Nurgaliyev Turgali Sarsengali uli; Salimov Ilxom Khaitovich (American Journal of Biology and Natural Sciences, 2026)
This article examines the epizootic status of Bradzot disease in sheep, conducted in a number of sheep farms. Several factors affecting the development of Bradzot disease, clinical signs, pathological and anatomical changes, bacteriological examination and laboratory studies on experimental animals are described. was taken into account.